The Question of the Legal Nature and Status of Real Estate Objects for Religious Purposes (Stato, Chiese e pluralismo confessionale, 2016)
Article peer evaluatedSUMMARY: 1. Introduction – 2. Degree of the subject study – 3. - Legal framework, empirical, and other source basis of the research – 4. Conclusions.ABSTRACT: The article is devoted to research of the texts of foreign laws, regulations, and concordats on property relations between the state and religious institutions, on property rights of religious institutions and property relations in religious institutions (regarding property objects for religious purposes), on the status of some property objects for religious purposes. The author of the research analyzed the features of legal and contractual regulation of property relations of religious institutions and the status of property objects for religious purposes. The methodological foundation of the research presented has comparative and legal research method as the basis.